Groundwater flow modeling in the basaltic hard rock area of Maharashtra, India - Chaitanya B. Pande; Kanak N. Moharir; Sudhir Kumar Singh; Ahmed Elbeltagi; Quoc Bao Pham; Balamurugan Panneerselvam; Abhay M. Varade; Saber Kouadri (Applied Water Science, 2021)
Abstract The ecological sustainable development and planning of groundwater resources is an excessive challenge for many countries currently facing water insufficiency. The main focus of this work was to determine the direction of groundwater flow, head value, and water level using the steady-state finite difference model (MODFLOW software) in basaltic formations in Maharashtra, India. The MODFLOW model was integrated with ground data using Geographic Information System (GIS) for sustainable groundwater resource management in the hard rock terrain. The MODFLOW-2005 model simulated the interaction between heads and time in 2014–18 by steady-state conditions. In this present study, four observation wells were selected. During the field survey, four observation wells have been monitored regularly as per the Central Groundwater Board guidelines. MODFLOW software has been conceptualized as a double-layered rigid and fractured aquifer area feast over 18,312 m × 11,265 m area. This research demonstrates that the integration of GIS, conventional fieldwork, and mathematical model can  support to understand groundwater demand and supply in a better way.